M-PASPORT DIGITAL APPLICATION-BASED PUBLIC SERVICE SYSTEM REFORM - Putu Adelya Pradnyandari; Luh Putu Mahyuni (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2024)
Electronic Government, or E-Government, is an information and communication application system that is increasingly being adopted in the government sector in line with technological advancements. The utilization of information technology in governance aids in simplifying the execution of governmental functions as providers of public services. This study delves into the changes or reforms implemented by the TPI Denpasar Class I Immigration Office, under the auspices of the Directorate General of Immigration, utilizing technological advancements in passport services through the M-Paspor digital application. The objective of this study is to analyze the implementation, readiness, inhibiting factors, and evaluate the usage of the M-Paspor application at the Immigration Office Class I TPI Denpasar. The method employed in this study is a qualitative approach with data collection through observation, interviews, and document studies. The study's outcomes reveal that the readiness to implement service through the M-Paspor application at the Denpasar Immigration Office is still suboptimal in accordance with the E-Government Readiness theoretical framework. Factors such as communication infrastructure, connectivity levels, human resource readiness, budget allocation, legal framework, and paradigm shift still require enhancement. Challenges in implementing the M-Paspor application include inadequate application maturity due to frequent disruptions, low employee productivity, societal unpreparedness for change, and uneven information dissemination. Therefore, serious attention from the government is necessary to streamline digital transformation and implement M-Paspor in passport application services. Strategic actions are required to overcome these obstacles and ensure that technology's benefits are maximized in public services.